(untitled) - Gregory, Peter J. (Oxford, 2006)
The book expesses recent developments in techniques and an improved understanding of plant and soil interactions to present a comprehensive look at this important relationship. The book's content covers root response to and modification of soils; genetic control of roots responses to the environment; use of modern techniques in imaging, molecular biology and analytical chemistry; practical exploration of root characters
Keywords: Roots (Botany),Roots (Botany) Rễ (thực vật)